Plasmonics-based detection of H2 and CO: discrimination between reducing gases facilitated by material control - Dharmalingam, Gnanaprakash; Joy, Nicholas A.; Grisafe, Benjamin; Carpenter, Michael A. (Beilstein Journal of Nanotechnology, 2012)
Monitoring emissions in high-temperature-combustion applications is very important for regulating the discharge of gases such as NO2 and CO as well as unburnt fuel into the environment. This work reports the detection of H2 and CO gases by employing a metal–metal oxide nanocomposite (gold–yttria stabilized zirconia (Au–YSZ)) film fabricated through layer-by-layer physical vapor deposition (PVD). The change in the peak position of the localized surface plasmon resonance (LSPR) was monitored as a function of time and gas concentration. The responses of the films were preferential towards H2, as observed from the results of exposing the films to the gases at temperatures of 500 °C in a background of dry air. Characterization of the samples by XRD and SEM enabled the correlation of material properties with the differences in the CO- and H2-induced LSPR peak shifts, including the relative desensitization towards NO2. Sensing characteristics of films with varying support thicknesses and metal-particle diameters have been studied, and the results are presented. A comparison has been made to films fabricated through co-sputtered PVD, and the calibration curves of the sensing response show a preferential response towards H2. The distinction between H2 and CO responses is also seen through the use of principal-component analysis (PCA). Such material arrangements, which can be tuned for their selectivity by changing certain parameters such as particle size, support thickness, etc., have direct applications within optical chemical sensors for turbine engines, solid-oxide fuel cells, and other high-temperature applications.
Keywords: hydrogen detection; nanocomposites gold nanoparticles; optical sensor; plasmonics; physical vapor deposition; surface plasmon resonance